Pengaruh Modal, Alokasi Jam Kerja, dan Lama Usaha Terhadap Pendapatan Pengusaha Bidang Industri Genteng di Desa Darmasaba - I Putu Junior Surya Ananda; Ida Bagus Putu Purbadharmaja (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Badung Regency is one of the regencies/cities in Bali Province with significant potential in the small industry sector, particularly within several Micro, Small, and Medium Enterprises (MSMEs) spread across various areas in Badung Regency. One example is Darmasaba Village, which is home to 35 small-scale tile manufacturing businesses scattered across different banjars within the village. This indicates that Darmasaba Village has a substantial number of tile industries that continue to thrive in the Abiansemal District of Badung Regency. However, over time, the clay tile industry has experienced a decline due to the availability of many alternative materials, such as concrete roofs, metal tiles, aluminium roofs, and UPVC (Unplasticised Polyvinyl Chloride) roofs. The objectives of this study are (1) to analyse the simultaneous effects of capital, work hours allocation, and business age on the income of tile manufacturers in Darmasaba Village, and (2) to analyse the partial effects of capital, work hours allocation, and business age on the income of tile manufacturers in Darmasaba Village. The data used are primary, with 35 respondents participating. The analysis technique employed is multiple linear regression. The results indicate that (1) capital, work hours allocation, and business age have a significant simultaneous effect on the income of tile manufacturers in Darmasaba Village; (2) capital and business age have a positive and significant effect on the income of tile manufacturers in Darmasaba Village; (3) work hours allocation has a negative and significant effect on the income of tile manufacturers in Darmasaba Village.